Where do they care? The ECB in the media and inflation expectations - Vegard Høghaug Larsen; Nicolò Maffei-Faccioli; Laura Pagenhardt (Norges Bank, 2023)
This paper examines how news coverage of the European Central Bank (ECB) affects consumer inflation expectations in the four largest euro area countries. Utilizing a unique dataset of multilingual European news articles, we measure the impact of ECB-related inflation news on inflation expectations. Our results indicate that German and Italian consumers are more attentive to this news, whereas in Spain and France, we observe no significant response. The research underscores the role of national media in disseminating ECB messages and the diverse reactions among consumers in different euro area countries.
hdl:11250/3073358
Keywords: D80; E32; E66; 330; ECB; Inflation expectations; News coverage; Textual analysis